2019
DOI: 10.1038/s41586-019-1375-0
|View full text |Cite
|
Sign up to set email alerts
|

Giant thermal Hall conductivity in the pseudogap phase of cuprate superconductors

Abstract: The nature of the pseudogap phase of cuprates remains a major puzzle. Although there are indications that this phase breaks various symmetries, there is no consensus on its fundamental nature 1 . Although Fermi-surface 2 , transport 3 and thermodynamic 4 signatures of the pseudogap phase are reminiscent of a transition into a phase with antiferromagnetic order 5,6 , there is no evidence for an associated long-range magnetic order. Here we report measurements of the thermal Hall conductivity κ xy in the normal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
158
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(175 citation statements)
references
References 41 publications
15
158
2
Order By: Relevance
“…In this paper, we show that although thermal Hall conductance is not a well-defined bulk transport coefficient, the difference of thermal Hall conductances of two 2d materials 1 We use the notation κ A instead of the more standard κ xy to avoid confusion with the off-diagonal component of κ S which may be nonzero if rotational invariance is broken. 2 For gapped 2d systems at low temperatures, one can try to define thermal Hall conductance as the coefficient of the gravitational Chern-Simons term in the low-energy effective action [7][8][9]. As explained in [5], the energy current corresponding to the gravitational Chern-Simons term is of higher order in derivatives, in agreement with the above discussion.…”
Section: Introduction and Overviewsupporting
confidence: 56%
See 1 more Smart Citation
“…In this paper, we show that although thermal Hall conductance is not a well-defined bulk transport coefficient, the difference of thermal Hall conductances of two 2d materials 1 We use the notation κ A instead of the more standard κ xy to avoid confusion with the off-diagonal component of κ S which may be nonzero if rotational invariance is broken. 2 For gapped 2d systems at low temperatures, one can try to define thermal Hall conductance as the coefficient of the gravitational Chern-Simons term in the low-energy effective action [7][8][9]. As explained in [5], the energy current corresponding to the gravitational Chern-Simons term is of higher order in derivatives, in agreement with the above discussion.…”
Section: Introduction and Overviewsupporting
confidence: 56%
“…There has been much theoretical as well as experimental interest in thermal Hall conductivity and conductance of various materials. Just to give a couple of recent examples: (1) thermal Hall conductance has been used to probe the non-Abelian nature of the ν = 5/2 FQHE state [1]; (2) an unusual behavior of thermal Hall conductivity at low temperatures was observed in cuprate superconductors in the pseudogap region [2]. Despite many theoretical works on the thermal Hall effect (see e.g.…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…Recent studies of the metallic state of high-T c cuprate superconductors, such as La 1.6−x Nd 0.4 Sr x CuO 4 (Nd-LSCO), obtained by suppressing superconductivity using magnetic fields, indicate a very interesting trend in the thermal Hall coefficient [2] as a function of doping. On the overdoped side, with a hole doping of p > p * , where p * corresponds to the doping value where the pseudogap temperature vanishes, the thermal Hall conductivity κ xy obeys the WF law for low T .…”
Section: Introductionmentioning
confidence: 99%
“…The large κ xy observed at dopings with and without Néel order suggests that magnons are not responsible for this phenomenon. Further, Grissonnanche et al [2] argue that the observed magnitude of κ xy at low temperatures is too large to be explained by spin-scattered phonons. This prompts the rather intriguing possibility of emergent neutral excitations that are responsible for this unusual behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation